2008
DOI: 10.1007/s11126-008-9071-5
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid Anxiety in Bipolar Disorder Alters Treatment and Prognosis

Abstract: Mood disorders in general, and bipolar disorder in particular, are unique among the psychiatric conditions in that they are associated with extraordinarily high rates of comorbidity with a multitude of psychiatric and medical conditions. Among all the potential comorbidities, co-occurring anxiety disorders stand out due to their very high prevalence. Outcome in bipolar illness is worse in the presence of a comorbid anxiety disorder. The coexistence of an anxiety disorder presents a particularly difficult chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 108 publications
3
45
1
Order By: Relevance
“…The negative impacts of comorbid anxiety have been suggested in previous studies. 16,20 Our study confirms this impact in a large, nationally representative sample that includes the nonhelp-seeking population and identifies the unique predictors of anxiety comorbidity. The specific predictors of comorbid anxiety disorders illustrate the importance of the issue: people with a comorbid anxiety disorder are more likely to have experienced an MDE or a manic episode during the past 12 months when controlling for the remaining variables.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The negative impacts of comorbid anxiety have been suggested in previous studies. 16,20 Our study confirms this impact in a large, nationally representative sample that includes the nonhelp-seeking population and identifies the unique predictors of anxiety comorbidity. The specific predictors of comorbid anxiety disorders illustrate the importance of the issue: people with a comorbid anxiety disorder are more likely to have experienced an MDE or a manic episode during the past 12 months when controlling for the remaining variables.…”
Section: Discussionsupporting
confidence: 73%
“…13,16,[29][30][31] For example, ADs are the first line of treatment for anxiety disorders, but they can aggravate the side effects of mood stabilizers for many patients and can worsen or trigger mania. 13,16,30 Although new research has begun to identify some beneficial pharmacological treatments for comorbid anxiety, results remain preliminary and raise many questions. 32 Given the interactions between the characteristics of BD and the pharmacological treatment of anxiety, combined with the absence of robust research evidence showing efficacy, many have suggested that the psychological treatment of the anxiety disorder may be an interesting treatment alternative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22][23][24][25][26][27][28][29][30] Notably, treatment with lurasidone has previously demonstrated significant anxiolytic treatment effects in three separate 6-week trials in bipolar depression. [33][34][35] While further studies are necessary to confirm these findings, the results of the current analysis, taken together with the consistent improvements in HAM-A scores observed in prior bipolar depression studies, suggest that lurasidone may be a useful treatment for mixed forms of major depression associated with anxiety.…”
Section: Lurasidone For Mdd With Mixed Features and Anxiety 241mentioning
confidence: 99%
“…[10][11][12] High levels of anxiety have frequently been reported to reduce the likelihood of achieving an adequate antidepressant response in patients with both unipolar MDD [19][20][21][22][23][24][25][26][27] and bipolar depression. [28][29][30] To our knowledge, no controlled trial to date has evaluated the potential impact of concurrent anxiety symptoms on response to treatment in patients presenting with MDD with mixed features.…”
Section: Introductionmentioning
confidence: 99%